Bothros, Favissa und Co. – Von rituellen Löchern und ihren Bezeichnungen - Murgan, Andreas (Orte der Forschung, Orte des Glaubens. Neue Perspektiven für Heiligtümer in Italien von der Archaik bis zur Späten Republik. Akten der internationalen Tagung in Darmstadt am 19. und 20. Juli 2013, 2016)
In ancient sanctuaries it was a common phenomenon to sacrifice objects and deposit them as a gift for the gods. Therefore, it is not surprising that we often find traces of such dedications in the form of pits or similar contexts in the archaeological record. At a glance it is obvious that practices varied from case to case. Nonetheless, a proper terminology to describe this phenomenon has not developed in scholarship. On the contrary, the same feature is often described by different terms, whereas the same word can be applied to totally divergent examples. Many of the terms used give the impression that these were words used in antiquity. This paper examines a series of terms that are employed to describe the different contexts that contain depositions of dedicated objects. It demonstrates that current phraseology is not useful for advancing research on ancient sanctuaries, since it unnecessarily complicates communication on this topic. Instead we should pay more attention to the proper description and analysis of features, foregoing confusing terms, in order to open up new debate in this still neglected field of research.